2010
DOI: 10.1074/jbc.m110.161984
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Cysteine 179 of IκBα Kinase by Nimbolide Leads to Down-regulation of NF-κB-regulated Cell Survival and Proliferative Proteins and Sensitization of Tumor Cells to Chemotherapeutic Agents

Abstract: Reverse pharmacology, also called the "bedside to bench" approach, that deals with new uses for a well known molecular entity has been used extensively in cancer drug development to identify novel compounds and delineate their mechanisms of action. Here, we show that nimbolide, a triterpenoid isolated from Azadirachta indica,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 45 publications
5
104
0
Order By: Relevance
“…Nimbolide (33), butein (43), 3-formylchromone (44), and other compounds have been reported to exhibit similar effects on Cys 179 . In addition, we found that piperlongumine also blocked the phosphorylation of serine 181 and tyrosine 188 in IKKb induced by TNFa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nimbolide (33), butein (43), 3-formylchromone (44), and other compounds have been reported to exhibit similar effects on Cys 179 . In addition, we found that piperlongumine also blocked the phosphorylation of serine 181 and tyrosine 188 in IKKb induced by TNFa.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that inhibition of NF-kB activation by piperlongumine does not suppress DNA binding directly. This compound may, however, use the inhibitory mechanism of nimbolide (33) and g-tocotrienol (34), which inhibit NF-kB activation indirectly.…”
Section: Piperlongumine Does Not Directly Affect the Binding Of Nf-kbmentioning
confidence: 99%
“…Electrophoretic Mobility Shift Assay. To examine NF-B activation in leukemia and myeloma cells, nuclear extracts were prepared and an EMSA was performed using these extracts (Gupta et al, 2010c). The EMSAs for AP-1 and Oct-1 were performed as described for NF-B using 32 P end-labeled doublestranded oligonucleotides.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the effect of bharangin on TNF-␣-induced invasion, the BD BioCoat tumor invasion system (BD Biosciences, San Jose, CA) was used employing a method as described previously (Gupta et al, 2010c).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, resveratrol was found to inhibit proliferation and induce apoptosis in several human tumor cells (7,8). It has been previously reported that resveratrol can inhibit the growth of malignant B-cell lines in a dose-and timedependent manner (9,10). However, EBV infection might confer additional survival potential to malignant B cells, also depending on the different programs of latent gene expression adopted by the virus.…”
Section: Introductionmentioning
confidence: 99%